Development of combined medium for in-vitro co-culture of mesenchymal stem cell and pseudomonas aeruginosa. (14th October 2020) - Lim, Poon Nian; Tong, Shi Yun; Zhao, Zixuan; Ho, Bow; Wang, Wilson; Han, Jing; Thian, Eng San
ABSTRACT: A co-culture of cells, bacteria and biomaterial could effectively test the performance of antibacterial biomaterials in infection states that mimic actual clinical conditions. As cultivating environments of cells and bacteria vary in many aspects, the development of a suitable co-culture medium is required for the co-culturing of bacteria and cells. The aim of this study was to develop a suitable combined medium for co-culturing of human bone marrow-derived mesenchymal stem cells (BMSCs) and Pseudomonas aeruginosa ( P. aeruginosa ). Combined medium at different ratios of Dulbecco's modified eagle medium containing 10% fetal bovine serum (D10) and mueller hinton broth were prepared. From the evaluation of cell morphology, growth, viability, bone differentiation, and bacteria growth, the ratio of 75% D10 and 25% mueller hinton broth was suggested to be favourable in supporting the co-culturing of BMSCs and P. aeruginosa .